More than just a (red) list: Over a decade of using South Africa's threatened ecosystems in policy and practice. (June 2020) - Botts, Emily Anne; Skowno, Andrew; Driver, Amanda; Holness, Stephen; Maze, Kristal; Smith, Tammy; Daniels, Fahiema; Desmet, Philip; Sink, Kerry; Botha, Mark; Nel, Jeanne; Manuel, Jeffrey
Abstract: One of the stated applications of the IUCN Red List of Ecosystems (RLE) is to influence government policy and decision-making. We share 15 years' experience in integrating an independently developed indicator of ecosystem threat status into government policies and practice. South Africa's ecosystem threat status indicator was conceptualised in the early 2000s and progressed from a project-based indicator to listing of threatened ecosystems in terms of national legislation in 2011. We show the range of applications of the indicator, from its use as a headline indicator in the National Biodiversity Assessment to its role as a direct trigger for Environmental Impact Assessment. The strong link between threatened ecosystems and systematic conservation planning in South Africa also enabled ecosystem threat status to inform multi-sectoral development planning and decision-making. We show how bridging products, data availability, persistent mainstreaming and stakeholder engagement have encouraged the use of the indicator in government policy. The advantages and disadvantages of legislative listing are shared. Sound scientific foundations, combined with pragmatism, have provided a policy-relevant tool for focussing management on threatened ecosystems. We make active recommendations that will facilitate the policy uptake of the IUCN RLE in other countries.